A polylactic acid, polybutylene succinate composite material for a straw and a preparation method thereof
Patent Information
- Application Number
- CN202311262241.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-09-27
AI Technical Summary
但反应性挤出过程时间短,反应程度难控制,流动性易降低,且伴随副反应易产生刺激性气味
[0027]1、本发明制备了一种具有核壳结构PBS-CO-PLLA共聚酯,可作为PBS与PLA复合材料的非反应型相容剂及成核剂;一方面此共聚酯可通过两步聚合过程的投料及反应时间控制PBS链段与PLLA链段的质量比,形成不同粒径的具有核壳结构的共聚酯;另一方面相对于目前通过扩链剂及催化剂提高材料的相容性,共聚酯相容剂具有以下优异效果,共聚酯PBS及PLLA链段可分别与PBS/PLA复合材料对应基材相容形成纠缠结构,提高材料的界面强度和相容性,且此过程为物理相容无化学反应发生,无副产物产生,不产生刺激性气味;并且材料的分子量不会上升导致熔指降低影响材料的加工性能;此外共聚酯中单分散纳米粒子与多条聚乳酸分子链相连可诱导异相成核,加快结晶速度。
Smart Images

Figure CN117186610B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of environmentally friendly biodegradable materials, specifically relating to a polylactic acid and polybutylene succinate composite material for straws and its preparation method. Background Technology
[0002] Polylactic acid (PLA) is produced by ring-opening polymerization of lactic acid from fermented corn starch, tapioca starch, and straw, etc. It originates from renewable resources and can be biodegraded into environmentally friendly substances such as water and carbon dioxide. PLA possesses high strength, high modulus, and is easy to process and safe, making it suitable for applications such as disposable tableware, hotel supplies, and packaging materials. However, its poor toughness and low heat resistance severely limit its application range.
[0003] The monomers of polybutylene succinate (PBS) are mainly derived from petrochemicals, but it has good toughness, heat resistance, crystallinity and biodegradability.
[0004] Polybutylene succinate (PBS) is frequently added to polylactic acid (PLA) to improve the material's toughness, heat resistance, and processing properties. However, PBS and PLA are thermodynamically incompatible blends with weak interfacial forces, making them prone to phase separation. When the PBS content is low, it can act as rubber particles dispersed within a rigid PLA matrix, providing toughening through deformation, debonding from the matrix, and shear yielding, thus absorbing external forces. However, as the PBS content increases, the PBS particle size increases, and phase separation intensifies. External forces cannot be effectively transferred from the PLA matrix to the PBS particles, resulting in a decrease in toughening effect. Improving the compatibility between PLA and PBS can effectively enhance the toughening effect of PBS on PLA.
[0005] To address the aforementioned technical challenges in toughening PLA with PBS, existing improvements mainly involve adding chain extenders and catalysts, and reacting with the end groups of PLA and PBS through reactive extrusion. These technical solutions can improve the compatibility of PBS and PLA to some extent, but the performance of the composite material still has certain defects.
[0006] Chinese patents such as CN113354929A, CN108948694A, CN114213824A, CN 114752198 A, and CN116162339A utilize chain extenders such as polyepoxides, polyepoxy group-containing prepolymers, dianhydrides, compounds containing polyanhydride groups, isocyanates, polyisocyanate prepolymers, pyromellitic dianhydrides, triglycidyl isocyanate, and dicumyl peroxide, or catalysts such as monobutyltin triisooctanoate and dibutyltin dilaurate, to react with the end groups of PLA and PBS, thereby improving the compatibility of PBS and PLA and enhancing the performance of the composite material. However, reactive extrusion processes are short, the degree of reaction is difficult to control, flowability is easily reduced, and side reactions can easily produce an irritating odor. Summary of the Invention
[0007] To address the shortcomings of existing technologies, the present invention aims to provide a polylactic acid and polybutylene succinate composite material for straws and its preparation method, thereby solving the problems in the prior art.
[0008] The objective of this invention can be achieved through the following technical solutions:
[0009] A polylactic acid and polybutylene succinate composite material for straws comprises the following raw materials in parts by weight: 30-75 parts of polylactic acid, 10-40 parts of polybutylene succinate, 5-10 parts of core-shell structured PBS-CO-PLLA copolyester, and 10-20 parts of inorganic minerals.
[0010] Furthermore, the structural formula of the core-shell structured PBS-CO-PLLA copolyester is as follows:
[0011]
[0012] Furthermore, the inorganic mineral is at least one of silica, talc and calcium carbonate, and has a particle size of 5-10 μm.
[0013] A method for preparing a polylactic acid and polybutylene succinate composite material for straws includes the following steps:
[0014] Step 1: By weight, add 30-75 parts of polylactic acid, 10-40 parts of polybutylene succinate, 5-10 parts of core-shell structured PBS-CO-PLLA copolyester and 10-20 parts of inorganic minerals to a high-speed mixer and mix at 500-800 rpm for 3 minutes.
[0015] Step 2: The mixture is fed into a parallel twin-screw extruder and melt-extruded into granules to obtain polylactic acid and polybutylene succinate composite material for straws.
[0016] Furthermore, the main motor speed of the parallel twin-screw extruder is 200-300 rpm, and the temperature settings for each zone are as follows: Zone 1 150-170℃, Zone 2 170-190℃, Zone 3 175-195℃, Zone 4 175-195℃, Zone 5 175-195℃, Zone 6 175-195℃, Zone 7 175-195℃, Zone 8 170-190℃, Zone 9 170-190℃, Zone 10 170-190℃, Zone 11 170-190℃, Zone 12 170-190℃, Zone 13 180-200℃, Zone 14 180-200℃. Among them, the eighth and eleventh sections of the screw barrel are vacuumed with a vacuum degree of 0.08MPa. After extrusion, the strip is water-cooled, pelletized, and then dried until the moisture content is below 500ppm.
[0017] A core-shell structured PBS-CO-PLLA copolyester, with the following structural formula:
[0018]
[0019] The preparation method of the above-mentioned core-shell structured PBS-CO-PLLA copolyester includes the following steps:
[0020] S1, anhydrous ethanol, tetraethyl orthosilicate and deionized water are added to a container in sequence and stirred to obtain a mixture. Then, a mixture of ammonia and anhydrous ethanol is added dropwise to the mixture. After stirring, filtration and drying, monodisperse nanoparticles are obtained.
[0021] S2, under a nitrogen atmosphere and stirring conditions, monodisperse nanoparticles were dispersed in a 1,4-succinic acid solution and reacted in an oil bath at 140-150℃. Then, 1,4-butanediol and tetrabutyl titanate were added, and esterification was carried out under normal pressure. The pressure was then reduced to 0.1 MPa, the temperature was raised to 200-210℃, and tetrabutyl titanate was added to react, resulting in a PBS polymer of monodisperse nanoparticles coated with 1,4-butanediol and 1,4-succinic acid prepolymer.
[0022] S3, L-lactide, PBS prepolymer and stannous octoate are added to a reaction vessel, the vessel is sealed and protected with nitrogen, the oil bath is heated to 130°C for prepolymerization, and then the temperature is raised to 150-160°C for reaction to obtain a core-shell polymer of PBS-CO-PLLA-coated nanoparticles.
[0023] Furthermore, in S2, the molar ratio of 1,4-butanediol, 1,4-succinic acid, and tetrabutyl titanate is 1.1:1:0.05 to 0.1.
[0024] Furthermore, in S3, the mass ratio of L-lactide, PBS prepolymer, and stannous octoate is 1:1 to 6:0.05.
[0025] Application of core-shell structured PBS-CO-PLLA copolyester as a compatibilizer in the preparation of straw composite materials.
[0026] The beneficial effects of this invention are:
[0027] 1. This invention prepares a PBS-CO-PLLA copolyester with a core-shell structure, which can be used as a non-reactive compatibilizer and nucleating agent for PBS / PLA composite materials. On the one hand, this copolyester can control the mass ratio of PBS segments to PLLA segments through a two-step polymerization process, forming copolyesters with core-shell structures of different particle sizes. On the other hand, compared with the current method of improving material compatibility through chain extenders and catalysts, the copolyester compatibilizer has the following excellent effects: the PBS and PLLA segments of the copolyester can respectively form entangled structures with the corresponding substrates of PBS / PLA composite materials, improving the interfacial strength and compatibility of the materials. Moreover, this process is a physical compatibility process without chemical reaction, without by-products, and without producing an irritating odor. Furthermore, the molecular weight of the material will not increase, leading to a decrease in melt index and affecting the processing performance of the material. In addition, the monodisperse nanoparticles in the copolyester connected with multiple polylactic acid molecular chains can induce heterogeneous nucleation and accelerate the crystallization rate.
[0028] 2. The polylactic acid / polybutylene succinate material for straws prepared by this invention has high toughness and excellent heat resistance. After annealing, the heat distortion temperature can reach 98°C. The material has no irritating odor, and the melt index is controllable and easy to process, which can improve the pain points in the current straw material usage process. Attached Figure Description
[0029] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0030] Figure 1 The structural formula of the core-shell PBS-CO-PLLA copolyester is shown;
[0031] Figure 2 The synthetic route of the core-shell structured PBS-CO-PLLA copolyester is shown. Detailed Implementation
[0032] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0033] The straw is made of polylactic acid and polybutylene succinate composite material, synthesized from polylactic acid, polybutylene succinate, inorganic minerals, and a core-shell structured PBS-CO-PLLA copolyester; the structural formula of the core-shell structured PBS-CO-PLLA copolyester is as follows. Figure 1 As shown;
[0034] The following examples illustrate this in detail. It is worth mentioning that, unless otherwise specified, the preparation processes in the following examples are all conventional methods in the prior art, and therefore will not be described in detail. All parts in the following embodiments refer to parts by mass.
[0035] Example 1
[0036] like Figure 2 As shown, the preparation process of the core-shell structured PBS-CO-PLLA copolyester includes:
[0037] (1) Preparation of monodisperse nanoparticles: 80 mL of anhydrous ethanol, 20 mL of tetraethyl orthosilicate and 10 mL of deionized water were added to the reaction vessel and stirred magnetically to obtain a mixed solution; then 10 mL of ammonia water and 10 mL of anhydrous ethanol were mixed and slowly added dropwise to the above mixed solution. The mixture was stirred magnetically at room temperature for 24 h, filtered and dried to obtain monodisperse nano silica particles.
[0038] (2) Under a nitrogen atmosphere and mechanical stirring, completely dried monodisperse nanoparticles were dispersed in a 1,4-succinic acid solution and reacted in an oil bath at 140°C for 2 hours. Then, 1,4-butanediol and tetrabutyl titanate catalyst were added, wherein the molar ratio of 1,4-butanediol:1,4-succinic acid:catalyst was 1.1:1:0.05. The esterification reaction was carried out at atmospheric pressure for 4 hours. Then, the pressure was reduced to 0.1 MPa, the temperature was raised to 200°C, and tetrabutyl titanate catalyst with a molar ratio of 0.05% of 1,4-butanediol was added and reacted for 8 hours to obtain PBS polymers of monodisperse nanoparticles coated with 1,4-butanediol and 1,4-succinic acid prepolymer.
[0039] (3) L-lactide, PBS prepolymer and stannous octoate were added to the reaction vessel in a mass ratio of 1:1:0.05. The vessel was quickly sealed and protected with nitrogen gas. The mixture was heated in an oil bath to 130°C for 1 hour for prepolymerization, and then heated to 150°C for 3 hours to obtain a core-shell polymer of PBS-CO-PLLA-coated nanoparticles. The prepared core-shell crystalline copolyester was mainly composed of PBS shell.
[0040] Example 2
[0041] The preparation process of core-shell structured PBS-CO-PLLA copolyester includes:
[0042] (1) Preparation of monodisperse nanoparticles: 80 mL of anhydrous ethanol, 20 mL of tetraethyl orthosilicate and 10 mL of deionized water were added to the reaction vessel and stirred magnetically. Then, a mixture of 10 mL of ammonia and 10 mL of anhydrous ethanol was slowly added dropwise to the above mixture. The mixture was stirred magnetically at room temperature for 24 h. After filtration and drying, monodisperse nano silica particles were obtained.
[0043] (2) Under a nitrogen atmosphere and mechanical stirring, completely dry monodisperse nanoparticles were dispersed in a 1,4-succinic acid solution and reacted in an oil bath at 150°C for 2 hours. Then, 1,4-butanediol and tetrabutyl titanate catalyst were added. The preferred molar ratio of 1,4-butanediol:1,4-succinic acid:catalyst was 1.1:1:0.1. The esterification reaction was carried out at atmospheric pressure for 4 hours. Then, the pressure was reduced to 0.1 MPa, the temperature was raised to 210°C, and tetrabutyl titanate catalyst with a molar ratio of 0.1% of 1,4-butanediol was added and reacted for 3 hours to obtain PBS polymers of monodisperse nanoparticles coated with 1,4-butanediol and 1,4-succinic acid prepolymer.
[0044] (3) L-lactide, PBS prepolymer and stannous octoate were added to the reaction vessel in a mass ratio of 1:6:0.05. The vessel was quickly sealed and protected with nitrogen gas. The mixture was heated in an oil bath to 130°C for 1 hour for prepolymerization, and then heated to 160°C for 8 hours to obtain a core-shell polymer of PBS-CO-PLA-coated nanoparticles. The prepared core-shell crystalline copolyester was mainly composed of PLLA shell.
[0045] Example 3
[0046] Weigh the following raw materials by weight fraction: 30 parts polylactic acid, 40 parts polybutylene succinate, 10 parts of the core-shell structured PBS-CO-PLLA copolyester prepared in Example 2, and 20 parts of talc powder with a particle size of 5 μm.
[0047] The process of preparing polylactic acid and polybutylene succinate materials for straws using the above raw materials includes:
[0048] The above raw materials are sequentially added to a high-speed mixer and mixed at 800 rpm for 3 minutes. The mixture is then fed into a parallel twin-screw extruder with the main extruder speed at 300 rpm. The temperature settings for each zone are as follows: Zone 1 150-170℃, Zone 2 170-190℃, Zone 3 175-195℃, Zone 4 175-195℃, Zone 5 175-195℃, Zone 6 175-195℃, Zone 7... The temperature ranges from 175-195℃ in zone 8 to 170-190℃ in zone 9, 170-190℃ in zone 10, 170-190℃ in zone 11, 170-190℃ in zone 12, 180-200℃ in zone 13, and 180-200℃ in zone 14. The eighth and eleventh sections of the screw barrel are vacuumed with a vacuum degree of 0.08MPa. After extrusion, the strips are water-cooled, pelletized, and then dried until the moisture content is below 500ppm.
[0049] Example 4
[0050] Weigh the following raw materials by weight fraction: 38 parts polylactic acid, 40 parts polybutylene succinate, 7 parts of the core-shell structured PBS-CO-PLLA copolyester prepared in Example 2, and 15 parts of talc powder with a particle size of 5 μm.
[0051] The process of preparing polylactic acid and polybutylene succinate materials for straws using the above raw materials includes:
[0052] The above raw materials are sequentially added to a high-speed mixer and mixed at 650 rpm for 3 minutes. The mixture is then fed into a parallel twin-screw extruder with the main extruder speed set at 250 rpm. The temperature settings for each zone are as follows: Zone 1 150-170℃, Zone 2 170-190℃, Zone 3 175-195℃, Zone 4 175-195℃, Zone 5 175-195℃, Zone 6 175-195℃, Zone 7... The temperature ranges from 175-195℃ in zone 8 to 170-190℃ in zone 9, 170-190℃ in zone 10, 170-190℃ in zone 11, 170-190℃ in zone 12, 180-200℃ in zone 13, and 180-200℃ in zone 14. The eighth and eleventh sections of the screw barrel are vacuumed with a vacuum degree of 0.08MPa. After extrusion, the strips are water-cooled, pelletized, and then dried until the moisture content is below 500ppm.
[0053] Example 5
[0054] Weigh the following raw materials by weight fraction: 45 parts polylactic acid, 40 parts polybutylene succinate, 5 parts of the core-shell structured PBS-CO-PLLA copolyester prepared in Example 2, and 10 parts of talc powder with a particle size of 5 μm.
[0055] The process of preparing polylactic acid and polybutylene succinate materials for straws using the above raw materials includes:
[0056] The above raw materials are sequentially added to a high-speed mixer and mixed at 500 rpm for 3 minutes. The mixture is then fed into a parallel twin-screw extruder with the main extruder speed set at 200 rpm. The temperature settings for each zone are as follows: Zone 1 150-170℃, Zone 2 170-190℃, Zone 3 175-195℃, Zone 4 175-195℃, Zone 5 175-195℃, Zone 6 175-195℃, Zone 7... The temperature ranges from 175-195℃ in zone 8 to 170-190℃ in zone 9, 170-190℃ in zone 10, 170-190℃ in zone 11, 170-190℃ in zone 12, 180-200℃ in zone 13, and 180-200℃ in zone 14. The eighth and eleventh sections of the screw barrel are vacuumed with a vacuum degree of 0.08MPa. After extrusion, the strips are water-cooled, pelletized, and then dried until the moisture content is below 500ppm.
[0057] Example 6
[0058] Weigh the following raw materials by weight fraction: 55 parts polylactic acid, 15 parts polybutylene succinate, 10 parts of the core-shell structured PBS-CO-PLLA copolyester prepared in Example 1, and 20 parts of talc powder with a particle size of 10 μm.
[0059] Using the same preparation process as in Example 3, polylactic acid and polybutylene succinate materials for straws were prepared using the above-mentioned raw materials.
[0060] Example 7
[0061] Weigh the following raw materials by weight fraction: 62 parts polylactic acid, 15 parts polybutylene succinate, 8 parts of the core-shell structured PBS-CO-PLLA copolyester prepared in Example 1, and 15 parts of talc powder with a particle size of 10 μm.
[0062] Using the same preparation process as in Example 4, polylactic acid and polybutylene succinate materials for straws were prepared using the above-mentioned raw materials.
[0063] Example 8
[0064] Weigh the following raw materials by weight fraction: 68 parts polylactic acid, 15 parts polybutylene succinate, 7 parts of the core-shell structured PBS-CO-PLLA copolyester prepared in Example 1, and 10 parts of talc powder with a particle size of 10 μm.
[0065] Using the same preparation process as in Example 5, polylactic acid and polybutylene succinate materials for straws were prepared using the above-mentioned raw materials.
[0066] Example 9
[0067] Weigh the following raw materials by weight fraction: 75 parts polylactic acid, 10 parts polybutylene succinate, 5 parts of the core-shell structured PBS-CO-PLLA copolyester prepared in Example 1, and 10 parts of silica with a particle size of 8 μm.
[0068] Using the same preparation process as in Example 5, polylactic acid and polybutylene succinate materials for straws were prepared using the above-mentioned raw materials.
[0069] Comparative Example 1
[0070] Weigh the following raw materials by weight fraction: 40 parts polylactic acid, 45 parts polybutylene succinate, and 15 parts talc powder with a particle size of 10 μm.
[0071] Using the same preparation process as in Example 4, polylactic acid and polybutylene succinate materials for straws were prepared using the above-mentioned raw materials.
[0072] Comparative Example 2
[0073] Weigh the following raw materials in the following weight fractions: 40 parts polylactic acid, 45 parts polybutylene succinate, 15 parts talc powder with a particle size of 10 μm, and 0.3 parts BASF polyepoxy chain extender ADR-4468.
[0074] Using the same preparation process as in Example 4, polylactic acid and polybutylene succinate materials for straws were prepared using the above-mentioned raw materials.
[0075] Comparative Example 3
[0076] Weigh the following raw materials in the indicated weight fractions: 58 parts polylactic acid, 22 parts polybutylene succinate, 20 parts talc powder with a particle size of 5 μm, and 0.3 parts BASF polyepoxy chain extender ADR-4468.
[0077] Using the same preparation process as in Example 3, polylactic acid and polybutylene succinate materials for straws were prepared using the above-mentioned raw materials.
[0078] Comparative Example 4
[0079] Weigh the following raw materials in the indicated weight fractions: 70 parts polylactic acid, 20 parts polybutylene succinate, 10 parts silica with a particle size of 8 μm, and 0.3 parts methyl diphenyl diisocyanate.
[0080] Using the same preparation process as in Example 5, polylactic acid and polybutylene succinate materials for straws were prepared using the above-mentioned raw materials.
[0081] Experimental verification;
[0082] The composite materials obtained in Examples 3-9 and Comparative Examples 1-4 were injection molded into standard specimens, and their cantilever beam notched impact strength and heat distortion temperature were tested. The heat distortion temperature specimens of Examples 6-9 and Comparative Examples 3-4 were tested after annealing at 90°C for 10 min. The cantilever beam notched impact strength test method was in accordance with CB / T 1843, and the heat distortion temperature test method was in accordance with GB / T 1634. The melt flow index test method of the modified particles was in accordance with GB / T 3682. At the same time, the presence of irritating odor of the modified particles was evaluated. The test method was to take 50g of modified particles, put them into a 1L odor test bottle, seal it, treat it in an 80°C oven for 2 hours, take it out, and open the bottle when the temperature dropped to 60°C to evaluate the odor irritation.
[0083] The comparative test results of Examples 3-5 and Comparative Examples 1-2 are shown in Table 1 below:
[0084] Table 1 Comparative test results of Examples 3-5 and Comparative Examples 1-2
[0085]
[0086] The comparative test results of Examples 6-9 and Comparative Examples 3-4 are shown in Table 2 below:
[0087] Table 2 Comparative test results of Examples 6-9 and Comparative Examples 3-4
[0088]
[0089]
[0090] As shown in Table 1, by comparing Examples 3-9 with Comparative Examples 1-4, the overall performance of Examples 3-9 is significantly better than that of the Comparative Examples, specifically in terms of higher impact strength, higher heat distortion temperature, and the absence of irritating odor. Under the action of the core-shell structure PBS-CO-PLLA copolyester, the impact strength of PBS and PLA is significantly improved, and the melt index is moderate, meeting the requirements for straw extrusion molding. Therefore, the extrusion temperature of straws made from this material can be appropriately reduced to meet the toughness requirements of straw materials. Secondly, the material has a fast crystallization speed and a high heat distortion temperature, meeting the heat resistance requirements of both direct extrusion heat-resistant straws and crystallized straws. Comparative Example 1 lacks a chain extender, resulting in low impact resistance and a tendency for the produced straws to crack. Comparative Examples 2-4 used the polyepoxide chain extender ADR-4468 and the diisocyanate chain extender methyl diphenyl diisocyanate, which have lower melt indices, require higher processing temperatures, have higher current in the straw machine, and produce materials with an irritating odor.
[0091] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0092] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A polylactic acid and polybutylene succinate composite material for straws, characterized in that, The raw materials include the following parts by weight: 30-75 parts of polylactic acid, 10-40 parts of polybutylene succinate, 5-10 parts of core-shell structured PBS-CO-PLLA copolyester, and 10-20 parts of inorganic minerals. The preparation method of the core-shell structured PBS-CO-PLLA copolyester includes the following steps: S1, anhydrous ethanol, tetraethyl orthosilicate and deionized water are added to a container in sequence and stirred to obtain a mixture. Then, a mixture of ammonia and anhydrous ethanol is added dropwise to the mixture. After stirring, filtration and drying, monodisperse nanoparticles are obtained. S2, under a nitrogen atmosphere and stirring conditions, monodisperse nanoparticles were dispersed in a 1,4-succinic acid solution and reacted in an oil bath at 140-150℃. Then, 1,4-butanediol and tetrabutyl titanate were added, and esterification was carried out under normal pressure. The pressure was then reduced to 0.1 MPa, the temperature was raised to 200-210℃, and tetrabutyl titanate was added to react, resulting in a PBS polymer of monodisperse nanoparticles coated with 1,4-butanediol and 1,4-succinic acid prepolymer. S3, L-lactide, PBS prepolymer and stannous octoate are added to a reaction vessel, the vessel is sealed and protected with nitrogen, the oil bath is heated to 130°C for prepolymerization, and then the temperature is raised to 150~160°C for reaction to obtain a core-shell polymer of PBS-CO-PLLA-coated nanoparticles.
2. The polylactic acid and polybutylene succinate composite material for straws according to claim 1, characterized in that, The inorganic mineral is at least one of silica, talc and calcium carbonate, and has a particle size of 5-10 μm.
3. A method for preparing a polylactic acid and polybutylene succinate composite material for straws as described in claim 1 or 2, characterized in that, Includes the following steps: Step 1: By weight, add 30-75 parts of polylactic acid, 10-40 parts of polybutylene succinate, 5-10 parts of core-shell structured PBS-CO-PLLA copolyester and 10-20 parts of inorganic minerals to a high-speed mixer and mix at 500-800 rpm for 3 minutes. Step 2: The mixture is fed into a parallel twin-screw extruder and melt-extruded into granules to obtain polylactic acid and polybutylene succinate composite material for straws.
4. The method for preparing the polylactic acid and polybutylene succinate composite material for straws according to claim 3, characterized in that, The main motor speed of the parallel twin-screw extruder is 200-300 rpm, and the temperature settings for each zone are as follows: Zone 1 150-170℃, Zone 2 170-190℃, Zone 3 175-195℃, Zone 4 175-195℃, Zone 5 175-195℃, Zone 6 175-195℃, Zone 7 175-195℃, Zone 8 170-190℃, Zone 9 170-190℃, Zone 10 170-190℃, Zone 11 170-190℃, Zone 12 170-190℃, Zone 13 180-200℃, Zone 14 180-200℃. Among them, the eighth and eleventh sections of the screw barrel are vacuumed with a vacuum degree of 0.08MPa. After extrusion, the strip is water-cooled, pelletized, and then dried until the moisture content is below 500ppm.
5. A method for preparing a core-shell structured PBS-CO-PLLA copolyester, characterized in that, Includes the following steps: S1, anhydrous ethanol, tetraethyl orthosilicate and deionized water are added to a container in sequence and stirred to obtain a mixture. Then, a mixture of ammonia and anhydrous ethanol is added dropwise to the mixture. After stirring, filtration and drying, monodisperse nanoparticles are obtained. S2, under a nitrogen atmosphere and stirring conditions, monodisperse nanoparticles were dispersed in a 1,4-succinic acid solution and reacted in an oil bath at 140-150℃. Then, 1,4-butanediol and tetrabutyl titanate were added, and esterification was carried out under normal pressure. The pressure was then reduced to 0.1 MPa, the temperature was raised to 200-210℃, and tetrabutyl titanate was added to react, resulting in a PBS polymer of monodisperse nanoparticles coated with 1,4-butanediol and 1,4-succinic acid prepolymer. S3, L-lactide, PBS prepolymer and stannous octoate are added to a reaction vessel, the vessel is sealed and protected with nitrogen, the oil bath is heated to 130°C for prepolymerization, and then the temperature is raised to 150~160°C for reaction to obtain a core-shell polymer of PBS-CO-PLLA-coated nanoparticles.
6. The method for preparing the core-shell structured PBS-CO-PLLA copolyester according to claim 5, characterized in that, In S2, the molar ratio of 1,4-butanediol, 1,4-succinic acid and tetrabutyl titanate is 1.1:1:0.05~0.
1.
7. The method for preparing the core-shell structured PBS-CO-PLLA copolyester according to claim 5, characterized in that, In S3, the mass ratio of L-lactide, PBS prepolymer, and stannous octoate is 1:1 to 6:0.
05.
8. A core-shell structured PBS-CO-PLLA copolyester, characterized in that, It is prepared by the method described in any one of claims 5-7.
9. The application of the core-shell structured PBS-CO-PLLA copolyester of claim 8 as a compatibilizer in the preparation of straw composite materials.
Citation Information
Patent Citations
PLA / PBS conductive material and preparation method thereof
CN108948694A
Low-precipitation biodegradable PLA alloy, preparation method thereof and straw material
CN113354929A
Preparation method of heat-resistant PLA / PBS alloy material
CN114213824A
High-strength bio-based degradable PLA / PBS composite material for food packaging box and preparation method of high-strength bio-based degradable PLA / PBS composite material
CN114752198A
Heat-resistant and high-crystallinity PLA / PBS alloy material and preparation method thereof
CN116162339A
